MENGATASI KEJADIAN KEPUTIHAN PADA REMAJA PUTRI DI SMAN 2 RAMBAH HILIR - Nana Aldriana; Rahmi Fitria; Eka Yuli Handayani (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Vaginal discharge (Flour Albus) is a vaginal condition when removing fluid or mucus resembling pus. In Indonesia, around 90% of women experience vaginal discharge because The State of Indonesia is an area with a tropical climate, so fungi are easy to grow and develop, resulting in a lot of vaginal discharge in women in Indonesia. If not treated properly, vaginal discharge can be fatal, such as infertility, ectopic pregnancy (pregnant outside the womb) and is an early symptom of uterine cancer. The purpose of this study was to determine the factors related to the incidence of vaginal discharge at SMA N 2 Rambah Hilir This research method is carried out using a quantitative analytic research type with a cross sectional design. The sample was taken using the Proportional Random Sampling technique so that a large sample of 140 people was obtained. Data analysis was performed univariately, bivariately with chi-square and T-Independent tests. The results of this chi-square study are, pantyliner: Pvalue 0.003, vaginal cleanser: Pvalue 0.041, and the results of the T-Independent test are, body mass index (BMI): Pvalue 0.862 there is no meaningful relationship between BMI and the incidence of vaginal discharge, and personal hygiene:. The conclusion in this study is that there is a relationship between knowledge, pantyliners and vaginal cleansers.